The Human Antibody Response to the Influenza Virus Neuraminidase Following Infection or Vaccination - Madhusudan Rajendran; Florian Krammer; Meagan McMahon (Vaccines, 2021)
The influenza virus neuraminidase (NA) is primarily involved in the release of progeny viruses from infected cells—a critical role for virus replication. Compared to the immuno-dominant hemagglutinin, there are fewer NA subtypes, and NA experiences a slower rate of antigenic drift and reduced immune selection pressure. Furthermore, NA inhibiting antibodies prevent viral egress, thus preventing viral spread. Anti-NA immunity can lessen disease severity, reduce viral shedding, and decrease viral lung titers in humans and various animal models. As a result, there has been a concerted effort to investigate the possibilities of incorporating immunogenic forms of NA as a vaccine antigen in future vaccine formulations. In this review, we discuss NA-based immunity and describe several human NA-specific monoclonal antibodies (mAbs) that have a broad range of protection. We also review vaccine platforms that are investigating NA antigens in pre-clinical models and their potential use for next-generation influenza virus vaccines. The evidence presented here supports the inclusion of immunogenic NA in future influenza virus vaccines.